2019
DOI: 10.7150/thno.35125
|View full text |Cite
|
Sign up to set email alerts
|

Dual-responsive, Methotrexate-loaded, Ascorbic acid-derived Micelles Exert Anti-tumor and Anti-metastatic Effects by Inhibiting NF-κB Signaling in an Orthotopic Mouse Model of Human Choriocarcinoma

Abstract: Gestational trophoblastic neoplasia (GTN), the most aggressive form of which is choriocarcinoma, can result from over-proliferation of trophoblasts. Treating choriocarcinoma requires high doses of systemic chemotherapeutic agents, which result in nonspecific drug distribution and severe toxicity. To overcome these disadvantages and enhance chemotherapeutic efficacy, we synthesized redox- and pH-sensitive, self-assembling, ascorbic acid-derived (PEG-ss-aAPP) micelles to deliver the drug methotrexate (MTX). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Nanomedicine is an emerging, dynamic branch of therapeutics that continues to gain prominence as a viable treatment alternative for many cancers, including colon cancer (Zhang Q. et al, 2019). Nanomedicine encompasses the application of nanotechnology (construction of functional structures on the nanometer scale) to the treatment, diagnosis, monitoring, and control of biological systems (Yang et al, 2015; Li et al, 2019; Wei et al, 2019). This field has seen the development of a number of drug delivery platforms, including polymer-drug conjugates (Li and Wallace, 2008; Karolczak-Bayatti et al, 2019), liposomes (Paasonen et al, 2010; Shen and Ye, 2019), micelles (Dehghan Kelishady et al, 2014; Alliot et al, 2019), nanoshells (Huschka et al, 2012; Russo et al, 2019), and dendrimers (Modi et al, 2014; Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nanomedicine is an emerging, dynamic branch of therapeutics that continues to gain prominence as a viable treatment alternative for many cancers, including colon cancer (Zhang Q. et al, 2019). Nanomedicine encompasses the application of nanotechnology (construction of functional structures on the nanometer scale) to the treatment, diagnosis, monitoring, and control of biological systems (Yang et al, 2015; Li et al, 2019; Wei et al, 2019). This field has seen the development of a number of drug delivery platforms, including polymer-drug conjugates (Li and Wallace, 2008; Karolczak-Bayatti et al, 2019), liposomes (Paasonen et al, 2010; Shen and Ye, 2019), micelles (Dehghan Kelishady et al, 2014; Alliot et al, 2019), nanoshells (Huschka et al, 2012; Russo et al, 2019), and dendrimers (Modi et al, 2014; Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sitagliptin solution (100 mg/kg per day for 9 days) was administered by oral gavage ( 32 ). MTX was administered at a dose of 5 mg/kg every other day until day 20 by intraperitoneal injection ( 33 ). Phosphate buffered saline (PBS) was used as negative control.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that we could couple DRC with an appropriate carrier that would be responsive to metal ions such as Fe 2+ that are more abundant at hematoma sites than in normal tissue. As a drug delivery system, we focused on the calixarene macrocyle and its derivatives, which have antiviral, antibacterial, antifungal, antitubercular, anticancer, and anti-oxidant activities [10][11][12][13]. We have shown that a p-methylenebisphosphonic calix [4] arene derivative can assemble into micelles to form host-guest complexes with small molecules in the cavity, such as the drug carboplatin [14,15].…”
Section: Open Accessmentioning
confidence: 99%